Comparative Analysis between Conventional Learning and Problem-Based Learning (PBL) in the Aspect of Understanding Indonesian Vocabulary - Arozatulo Bawamenewi; Riska Sri Handayani; Krisnawati Bate’e; Testing Ilmiah Gulo (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Research shows that PBL, which places students as active subjects in learning by emphasizing problem solving, provides better results in improving vocabulary understanding compared to conventional learning. Students who engage in PBL tend to have higher scores because they are actively involved in the learning process, where they are faced with challenging problems and given the opportunity to find their own solutions. In an effort to increase the effectiveness of the learning process, the use of learning models is crucial. The right learning model plays an important role in achieving educational goals. The purpose of this article is to compare conventional learning models and Problem-Based Learning (PBL) in understanding Indonesian vocabulary. By using qualitative methods. However, there are several obstacles in implementing PBL, such as lack of familiarity of students and teachers with this model and time constraints. However, the effectiveness of a learning model does not only depend on the model itself, but is also influenced by various other factors such as student characteristics, the quality of teacher teaching, and school environmental conditions. Thus, selecting a learning model that suits students' needs and characteristics is the key to achieving effective learning goals and increasing understanding of Indonesian vocabulary.